Novel Insights Into the Anti-aging Role of Mitophagy - Markaki, M.; Palikaras, K.; Tavernarakis, N. (Int Rev Cell Mol Biol, 2018)
Aging is a complex biological process affecting almost all living organisms. Although its detrimental effects on animals' physiology have been extensively documented, several aspects of the biology of aging are insufficiently understood. Mitochondria, the central energy producers of the cell, play vital roles in a wide range of cellular processes, including regulation of bioenergetics, calcium signaling, metabolic responses, and cell death, among others. Thus, proper mitochondrial function is a prerequisite for the maintenance of cellular and organismal homeostasis. Several mitochondrial quality control mechanisms have evolved to allow adaptation to different metabolic conditions, thereby preserving cellular homeostasis and survival. A tight coordination between mitochondrial biogenesis and mitochondrial selective autophagy, known as mitophagy, is a common characteristic of healthy biological systems. The balanced interplay between these two opposing cellular processes dictates stress resistance, healthspan, and lifespan extension. Mitochondrial biogenesis and mitophagy efficiency decline with age, leading to progressive accumulation of damaged and/or unwanted mitochondria, deterioration of cellular function, and ultimately death. Several regulatory factors that contribute to energy homeostasis have been implicated in the development and progression of many pathological conditions, such as neurodegenerative, metabolic, and cardiovascular disorders, among others. Therefore, mitophagy modulation may serve as a novel potential therapeutic approach to tackle age-associated pathologies. Here, we review the molecular signaling pathways that regulate and coordinate mitophagy with mitochondrial biogenesis, highlighting critical factors that hold promise for the development of pharmacological interventions toward enhancing human health and quality of life throughout aging.
Markaki, MariaPalikaras, KonstantinosTavernarakis, NektariosengResearch Support, Non-U.S. Gov'tReviewNetherlandsInt Rev Cell Mol Biol. 2018;340:169-208. doi: 10.1016/bs.ircmb.2018.05.005. Epub 2018 Jun 20.
Keywords: *Aging; *Autophagosome; *Autophagy; *energy homeostasis; *metabolism; *Mitochondria; *Mitophagy; *Signal Transduction; Animals; Eukaryota/metabolism/physiology; Humans